Critical Thinking Levels among Eleventh-Grade Students in Muscat Governorate: Exploring Gender, Academic Discipline, and their Interplay - Al-Saidi, Fawziya Saif Ali; Al-Maamari , Saif Nasser (Dirasat: Educational Sciences, 2024)
Objectives: This study aims to investigate critical thinking levels among eleventh-grade students in Muscat Governorate. It seeks to explore any disparities based on variables of gender and academic discipline and the potential interaction between these factors. Methods: The study employs a descriptive analytical approach. Data was collected through a critical-thinking test comprising five subtests, each containing (30) items aimed at assessing five distinct skills: drawing conclusions, identifying assumptions, deduction, interpretation, and evaluating arguments. The study sample consists of (320) students selected using the stratified random sampling method. Results: The findings reveal that a substantial portion (71.3%) of students exhibited a moderate level of critical thinking. Sub-skills were ranked in the following order: evaluating arguments, identifying assumptions, interpretation, deduction, and finally drawing conclusions. The study also indicates statistically significant differences according to the variables of gender and academic discipline. Specifically, females demonstrated higher overall critical thinking levels and excelled in evaluating arguments, whereas differences in other skills were not statistically significant. Similarly, students following the advanced mathematics track showcased higher critical thinking levels, particularly in deduction and interpretation, with no significant differences in other skills. Notably, the interaction between gender and academic discipline did not significantly impact overall critical thinking levels, except for the skill of evaluating arguments. Conclusion: The study underscores the importance of prioritizing critical thinking and fostering its development among students.